Agrculture, Ecology And Environment - Pawan Kumar Bharti; Olubukola Oluranti Babalola (New Delhi Discovery, 2014)
This book provides comprehensive coverage of the fundamental principles and current practices and trents in the field of agriculture, ecology and biotechnology.
Environmental Polution Agriculture Ecology
Keywords: Environmental Polution; Agriculture Ecology